2009
DOI: 10.1007/s10800-009-0046-5
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electrokinetic removal of Cd and Zn from fine-grained soil

Abstract: Pulsed electrokinetics studies were carried out to optimize the removal of Zn and Cd from fine-grained soils and to observe the effects of varying the pulse frequency, pulse time ratio (on/off), and DC voltage gradient. Existing forms of heavy metals in the soil matrix were determined using a sequential extraction method. The strongly bound fraction (bound to organic matter and residuals) that is difficult to remove from the soil matrix comprised 74 and 62% of the total Zn and Cd, respectively. In the electrok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 26 publications
2
25
2
3
Order By: Relevance
“…Additionally, the pulsed technique allows for diffusion of H + and metal ions in the sediment. These are limited during electromigration (Reddy and Saichek, 2004;Ryu et al, 2010). It has been shown that more metals desorb from sediment particles during pulsed electric field application and are therefore + depending on the amount of sorbed metal ions (Reaction 1).…”
Section: Metal Ion Sorption Onto Different Sorbents That Act Asmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the pulsed technique allows for diffusion of H + and metal ions in the sediment. These are limited during electromigration (Reddy and Saichek, 2004;Ryu et al, 2010). It has been shown that more metals desorb from sediment particles during pulsed electric field application and are therefore + depending on the amount of sorbed metal ions (Reaction 1).…”
Section: Metal Ion Sorption Onto Different Sorbents That Act Asmentioning
confidence: 99%
“…To improve the heavy metal solubility, a large number of studies have been carried out (Yang and Lin, 1998;Ottosen et al, 2005;Yeung and Gu, 2011). These usually involve chemical addition in the system, but there are also those that use changes in process design to enhance metal solubility (Chung and Kamon, 2005;Chen et al, 2006;Hansen et al, 2007;Rojo and Cubillos, 2009;Rojo et al, 2010;Ryu et al, 2010;Rajić and Ugar cina Perović, 2011;Rajić et al, 2012). Besides improving the metal solubility, it is of great importance to prevent OH -ion penetration into the sediment.…”
mentioning
confidence: 99%
“…현재, 전기동력학적 정화에서 양극조와 음극 조에 전해질이나 추출액을 첨가하여 오염물의 제거효율을 높이는 방법 Kim et al, 2011a;Ryu et al, 2011), 펄스를 이용하여 오염물의 제거율을 높이고 전력소모량을 감소시키는 방법 Ryu et al, 2010), 생물학적 방법과 전기동력학적 방법을 결합한 하이브리드 공법 (Alshawabkeh et al, 1999 Table 3).…”
Section: 전기동력학적 정화기술은 양극과 음극의 전극에서 발생 하는 전기분해반응과 토양 내에서 진행되는 전기이동 전 unclassified
“…식물정화법은 처리기간이 길며 식물의 뿌리를 통 하여 중금속을 추출하기 때문에 적용 범위의 한계성을 지 니고 있다 Ryu et al, 2010). 이러 한 이유로 최근에는 점토와 같은 저투수성 토양에서도 중 금속 등의 오염물질 제거가 가능한 전기동력학적 정화기 술에 대한 연구가 활발히 이루어지고 있다 (Acar et al, 1995;Baek et al, 2007;Kim et al, 2009a;Park et al, 2009b;Ryu et al, 2009;Ryu et al, 2010;Kim et al, 2011a;Kim et al, 2012).…”
unclassified
“…However, these are only temporary solutions. Recently, electrokinetic (EK) treatment has been used as a method to remediate or control various contaminated media such as soils (Kim et al 2009a(Kim et al , 2009bOttosen et al 2006;Reddy and Chinthamreddy 2004;Reddy et al 2001;Ryu et al 2010;Zhou et al 2004), mine tailings Hansen et al 2005;Kim et al 2002a;Ryu et al 2009), and sludge (Kim et al 2002b;Park et al 2010). The major mechanisms responsible for the removal of contaminants in the EK treatment process are electromigration and electroosmosis (Acar and Alshawabkeh 1993;Acar et al 1995).…”
Section: Introductionmentioning
confidence: 99%